Cottonseed Cake: Effect on Serum and Hematological Parameters of Poultry Broiler Birds - Thakur, Archana; Katoch , Shivani; Mane, B. G. (International Journal of Livestock Research, 2019)
The study was conducted to evaluate the effect of the locally available non-dehulled cottonseed cake on various serum and hematological parameters in the chicken broiler birds under completely randomized block design. For this purpose, day old broiler chicks (n=108) were divided into 4 main treatment groups T0, T1, T2 and T3. Each treatment group was further divided in 3 replicates with 9 chicks in each. T0 served as standard control diet and was given standard corn- soy flake- groundnut based ration. Treatment T1 was given ration containing 20 per cent non-dehulled cottonseed cake and T2 was given ration containing 20 per cent fermented non-dehulled cottonseed cake whereas treatment T3 was given ration containing 20 per cent non-dehulled cottonseed cake with additional supplementation of ferrous sulphate (600ppm) and lysine (2%). All the four broiler diets were formulated and prepared conferring to ICAR (2013) standards. Supplementation of non-dehulled cottonseed cake did not show any significant variation in complete blood count except for total leukocyte count (TLC) which was significantly (P<0.05) higher in treatment T1. Plasma phosphorous, triglycerides, high density lipids (HDL), serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), total protein (TP) and albumin content were non-significant amongst control and other treatment groups. The average value of cholesterol (mg/dL) and low-density lipids (mg/dL) in blood plasma was significantly (P<0.05) higher in treatment T1 compared to control T0 and treatment T2. The average alkaline phosphatase (ALP) value in blood plasma was significantly (P<0.05) higher in treatment T2 compared to control group T0. The average value of calcium (mg/dL) in blood plasma was significantly (P<0.05) higher in T3 compared to T2 and numerically higher than control T0 and T1. The average value of iron (mg/dL) in blood plasma in control T0 was significantly (P<0.05) higher compared to treatment T2 and T3 and numerically higher than treatment T1. Thus, it was concluded that replacement of 20 per cent non-dehulled cottonseed cake available in the market as a protein replacer in feed of broiler birds has effect on some of the serum and hematological parameters i.e., TLC, cholesterol, low-density lipids (LDL), ALP, calcium and iron.